Effect of Cash Position on Financial Performance: A Survey of Selected Small Retail Enterprises in Nakuru City - Njoroge, Charles; Ombati, Robert M.; Wachira, Kelvin (The African Journal of Emerging Issues, 2025)
Purpose of the Study: The study was to determine the effect of cash position on the financial performance of selected small retail enterprises in Nakuru City, Kenya. Statement of the Problem: Small retail enterprises in Nakuru City often operate for years without significant growth, mainly selling similar, non-standard products. Many experience financial losses or minimal profitability, with low sales, return on equity, return on assets, and net profit margins. Methodology: The study utilized stratified random sampling to select 344 small retail enterprises from various sectors. Data was collected through structured questionnaires and analyzed using descriptive and inferential statistics. Descriptive statistics included frequencies, percentages, means, and standard deviations, while multiple linear regression was applied for hypothesis testing at a 5% significance level. Results of the Study: The study found that cash position was a significant predictor of financial performance among small retail enterprises in Nakuru City. Cash position was correlated to the financial performance of selected small retail enterprises in Nakuru City, Kenya.Conclusion and Policy Recommendation: The study concluded that cash position significantly influenced financial performance among small retail enterprises in Nakuru City. It recommended that these enterprises strategically manage liquidity, forecast receipts and payments, and assess the opportunity cost of cash and time value of money for better financial outcomes.
Keywords: Cash Management; Financial Performance; Retail Enterprise; Small Enterprise; Cash Position; Cash Planning; Kenya